The Implementation of Constitutional Court of Indonesia - Pandapotan, Jannes (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This study discusses The Implementation of Constitutional Court of Indonesia Decision No. 128/PUU XIII/2015 on the Elimination of Domicile Requirements for Village Apparatus Candidates in Pasar Batahan Village Batahan Sub-district Mandailing Natal District. This research was motivated by a decision of the Constitutional Court that removed the requirement of domicile for village apparatus candidates so village apparatus candidates could register anywhere without any regional restrictions. This type of research is field research with qualitative descriptive analysis methods. This method of data collection is by interview and documentation in accordance with the provisions in the constitutional court of Indonesia decision No. 128/PUU-XIII/2015 on the elimination of domicile requirements for village apparatus candidates in Pasar Batahan Village Batahan Sub-district Mandailing Natal District. The parties studied were the Head of Batahan Sub-district, Head of Pasar Batahan Village, Secretary of Pasar Batahan Village, Head of BPD of Pasar Batahan Village, Indigenous People of Pasar Batahan Village (Niniak Mamak) and Community Around Pasar Batahan Village as the voter of the place of implementation of the constitutional court decision related to the elimination of domicile requirements for village apparatus candidates. The results of the study mentioned that the implementation of constitutional court of Indonesia decision No. 128/PUU-XIII/2015 on the elimination of domicile requirements for village apparatus candidates in Pasar Batahan Village Batahan Sub-district Mandailing Natal District has been implemented this can be seen from the form of implementation that has been applied by the Village Head and Sub-District Head, namely by conducting socialization, networking, screening and appointment of village apparatus candidates conducted by the Village Head along with Sub-district Head. Then according to the view of Islamic Law has also been appropriate and there is no problem.